«Ignatian modernity» as legacy and opportunity in the face of civilizing challenges - Senent de Frutos, Juan Antonio (Razón y fe, 2019)
This is not a simple historical reading of the Ignatian and Jesuit tradition in the context of the crisis of modernity. It is rather a question of rescuing other historical possibilities insofar as they help us today to reconstruct paths of humanization that respond to or confront the limits of our postmodern indigencies. Thus, we try to make a hermeneutic contribution to it. This reading starts from the sense that the Jesuit and Ignatian social body gives today to its own cultural and historical tradition and how, from that tradition, we want to build bridges and work on the social and cultural frontiers of the global society from a convivial, dialogical and integrating vocation. The hypothesis we put forward is that a tradition such as the Jesuit and Ignatian tradition which today seeks an intercultural, interreligious and ecological qualified presence in the world, continues to be inspired by its original sources and can offer a cultura alternative to the logic of modernity because this alternative was already in its own sources.
Keywords: ignatian modernity; enlightenment; Ignatian cultural matrix; crisis of modernity; Society of Jesus